Low-temperature high-adhesion conductive silver paste and preparation method thereof
By preparing a low-temperature high adhesion conductive silver paste containing modified polyurethane and modified filler, the problems of unstable conductive pathways and poor adhesion effects after curing of the conductive silver paste are solved, and high adhesion under low temperature conditions are achieved Good electrical conductivity.
Patent Information
- Application Number
- CN202411942242.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-18
AI Technical Summary
At this stage, the conductive paths are unstable after the conductive silver paste are cured, the conductivity is poor, and the adhesion effect is poor.
Using a low-temperature, high adhesion conductive silver paste preparation method, the modified polyurethane, methyl methacrylate, isobornyl acrylate, acrylonitrile, KH570, photoinitiator, silver powder and ethyl acetate are mixed and The reaction was carried out to form a modified filler and a modified polyurethane, and finally hydroxyethyl acrylate and dibutyltin dilaurate were added, and the reaction was carried out to produce a low-temperature, high adhesion conductive silver paste.
It achieves high adhesion and good conductivity under low temperature conditions, enhances the dispersion and curing of silver powder, and extends the service life.
Smart Images

Figure BDA0005212793290000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-temperature conductive silver paste preparation, and in particular to a low-temperature high-adhesion conductive silver paste and a preparation method thereof. Background Art
[0002] In recent years, the electronic information manufacturing industry, such as integrated circuits, new display technologies, and the Internet of Things, has entered a rapid development stage. Its development tends to be intelligent, information-based, and lightweight, which requires new materials and technologies to gradually replace traditional tin-lead solder and copper foil circuit printing technology. Conductive silver paste is a key material in the fields of nano-conductive inks, printed circuits, and printed electronic devices. Silver powder of a single size and shape has a high conductivity. In order to obtain a highly conductive silver paste, the filling mass fraction of the silver powder is usually increased to 60-94%, but a high filling amount of the conductive phase will lead to a decrease in the bonding performance of the silver paste, which in turn affects the normal use of the conductive silver paste. Summary of the invention
[0003] The purpose of the present invention is to provide a low-temperature high-adhesion conductive silver paste and a preparation method thereof, which solves the problems that the conductive path of the conductive silver paste is unstable and has poor conductivity after curing, and the adhesion effect is poor.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a low-temperature high-adhesion conductive silver paste specifically comprises the following steps:
[0006] Step A1: the precursor, allyl alcohol, benzoin dimethyl ether and N,N-dimethylacetamide are uniformly mixed, and reacted for 1-1.5 hours at a rotation speed of 60-80 r / min and 365 nm ultraviolet light irradiation to obtain a modified filler;
[0007] Step A2: polycarbonate diol, isophorone diisocyanate and DMF are mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 60-70° C., and then a modified filler is added, and the reaction is continued for 3-5 hours, and hydroxyethyl acrylate and dibutyltin dilaurate are added, and the reaction is continued for 3-5 hours to obtain a modified polyurethane;
[0008] Step A3: Weigh the following raw materials in parts by weight: 10-15 parts of modified polyurethane, 10-15 parts of methyl methacrylate, 3-5 parts of isobornyl acrylate, 1-1.5 parts of acrylonitrile, 1-1.5 parts of KH570, 0.1-0.3 parts of photoinitiator, 55-65 parts of silver powder and 10-15 parts of ethyl acetate, mix the raw materials evenly, and prepare a low-temperature and high-adhesion conductive silver paste.
[0009] Furthermore, the molar ratio of the thiol group and allyl alcohol on the precursor in step A1 is 1:1, and the amount of benzoin dimethyl ether used is 2‰ of the mass of allyl alcohol.
[0010] Furthermore, the amount ratio of the polycarbonate diol, isophorone diisocyanate, modified filler and hydroxyethyl acrylate described in step A2 is 25mmo l:50mmo l:1.2g:18mmo l, the amount of dibutyltin dilaurate is 1‰ of the mass of hydroxyethyl acrylate, and the molecular weight of the polycarbonate diol is 1000.
[0011] Further, the precursor is prepared by the following steps:
[0012] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 60-80 r / min and a temperature of 105-110° C., stir for 3-5 hours, cool to 5° C., add triethylamine and p-toluenesulfonyl chloride, react for 20-25 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 60-80 r / min and a temperature of 140-150° C., react for 20-25 hours to obtain amino cellulose;
[0013] Step B2: Aminated cellulose, 3,4-dihydroxybenzaldehyde and N-methylpyrrolidone are mixed, stirred and potassium hydroxide is added at a speed of 120-150 r / min and a temperature of 25-30° C., and the mixture is reacted for 3-5 hours to obtain modified cellulose; 3,4-dimethoxytoluene, N-bromosuccinimide and carbon tetrachloride are mixed evenly, and the mixture is reacted for 10-15 minutes at a speed of 200-300 r / min and a temperature of 80-85° C.; azobisisobutyronitrile is added, and the mixture is reacted for 20-25 hours to obtain intermediate 1;
[0014] Step B3: The intermediate 1, thiourea and acetone are mixed evenly, reacted at a speed of 120-150 r / min and a temperature of 60-65° C. for 3-5 hours, and the filtrate is filtered to remove the filtrate, the substrate and the sodium hydroxide solution are mixed, and the reaction is carried out at a temperature of 100-110° C. for 10-12 hours to obtain a modified monomer, and the modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate and deionized water are mixed evenly, and the reaction is carried out at a speed of 150-200 r / min and a temperature of 85-90° C. for 10-15 hours, and the modified monomer is added, and the reaction is continued for 10-15 hours to obtain a precursor.
[0015] Furthermore, the mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mg: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0016] Furthermore, the molar ratio of the amino group on the aminated cellulose and 3,4-dihydroxybenzaldehyde in step B2 is 1:1, the amount of potassium hydroxide used is 1% of the mass of 3,4-dihydroxybenzaldehyde, and the amount ratio of 3,4-dimethoxytoluene, N-bromosuccinimide, carbon tetrachloride and azobisisobutyronitrile is 2.5g:2.5g:100mL:125mg.
[0017] Furthermore, the amount ratio of the intermediate 1, thiourea, acetone and sodium hydroxide solution in step B3 is 1.5 mmol:1.6 mmol:10 mL:15 mL, the mass fraction of the sodium hydroxide solution is 10%, and the amount ratio of modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate, deionized water and modified monomer is 1 g:2 g:4 g:100 mL:1.5 g.
[0018] Beneficial effects of the invention: A low-temperature high-adhesion conductive silver paste disclosed by the invention comprises the following raw materials: modified polyurethane, methyl methacrylate, isobornyl acrylate, acrylonitrile, KH570, a photoinitiator, silver powder and ethyl acetate; the modified polyurethane is taken as raw materials from a precursor and allyl alcohol; under ultraviolet light irradiation conditions, the thiol group on the precursor reacts with the double bond on the allyl alcohol to obtain a modified filler; polycarbonate diol and isophorone diisocyanate are reacted; the modified filler is used for chain extension; and finally, hydroxyethyl acrylate is used for end-capping to obtain the modified polyurethane.
[0019] The precursor uses cellulose as a raw material and is treated with p-toluenesulfonyl chloride, so that the hydroxyl group on the cellulose reacts with the acyl chloride on the p-toluenesulfonyl chloride to obtain pretreated cellulose, the pretreated cellulose is treated with ammonia water, so that the p-toluenesulfonic acid ester on the pretreated cellulose is ammoniolyzed to obtain aminated cellulose, the aminated cellulose is reacted with 3,4-dihydroxybenzaldehyde, so that the amino group on the aminated cellulose reacts with the aldehyde group on the 3,4-dihydroxybenzaldehyde to obtain modified cellulose, 3,4-methoxytoluene is reacted with N-bromosuccinimide, so that one hydrogen on the methyl group is replaced by bromine to obtain Intermediate 1, intermediate 1 is treated with thiourea to convert the bromine atom site on intermediate 1 into a thiol group to obtain a modified monomer, modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate and copper trifluoroacetylacetonate are mixed for reaction, the catechol structure on the modified cellulose and 2,3,6,7,10,11-hexahydroxytriphenylene hydrate can coordinate with copper ions to form a copper organic framework on the surface of the modified cellulose, and then the modified monomer is added, the modified monomer molecule also contains a catechol structure, and a copper organic framework containing a thiol group can be formed on the surface.
[0020] During the coating process, the conductive silver paste contains KH570, which can be decomposed with moisture in the air. The siloxane in the KH570 molecule can be hydrolyzed to produce silanol groups, which can increase the adhesion effect of the conductive silver paste. At the same time, the side chain of the polyurethane acrylate molecule produced after curing contains cyano groups. The cyano groups have high polarity, which can enhance the shrinkage performance of the molecular chain, reduce the distance between the silver powders, and adsorb the silver powder, which is beneficial to the dispersion of the silver powder. At the same time, the addition of modified fillers can form a stable conductive path in the silver paste, and increase the mechanical properties of the material after the silver paste is cured, thereby increasing the service life. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1: A method for preparing a low-temperature high-adhesion conductive silver paste, comprising the following steps:
[0023] Step A1: the precursor, allyl alcohol, benzoin dimethyl ether and N,N-dimethylacetamide are mixed uniformly, and reacted for 1 hour at a rotation speed of 60 r / min and irradiation with 365 nm ultraviolet light to obtain a modified filler;
[0024] Step A2: polycarbonate diol, isophorone diisocyanate and DMF are mixed, nitrogen is introduced for protection, and the mixture is reacted for 3 hours at a speed of 120 r / min and a temperature of 60° C., and then a modified filler is added and the reaction is continued for 3 hours, and then hydroxyethyl acrylate and dibutyltin dilaurate are added and the reaction is continued for 3 hours to obtain a modified polyurethane;
[0025] Step A3: Weigh the following raw materials in parts by weight: 10 parts of modified polyurethane, 10 parts of methyl methacrylate, 3 parts of isobornyl acrylate, 1 part of acrylonitrile, 1 part of KH570, 0.1 parts of photoinitiator, 55 parts of silver powder and 10 parts of ethyl acetate, mix the raw materials evenly, and prepare a low-temperature and high-adhesion conductive silver paste.
[0026] The molar ratio of the thiol group and allyl alcohol on the precursor described in step A1 is 1:1, and the amount of benzoin dimethyl ether used is 2‰ of the mass of allyl alcohol.
[0027] The amount ratio of the polycarbonate diol, isophorone diisocyanate, modified filler and hydroxyethyl acrylate described in step A2 is 25mmo l:50mmo l:1.2g:18mmo l, the amount of dibutyltin dilaurate is 1‰ of the mass of hydroxyethyl acrylate, and the molecular weight of the polycarbonate diol is 1000.
[0028] The model of the photoinitiator described in step A3 is DC369.
[0029] The precursor is prepared by the following steps:
[0030] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 60 r / min and a temperature of 105°C, stir for 3 hours, cool to 5°C, add triethylamine and p-toluenesulfonyl chloride, react for 20 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 60 r / min and a temperature of 140°C, react for 20 hours to obtain amino cellulose;
[0031] Step B2: Aminated cellulose, 3,4-dihydroxybenzaldehyde and N-methylpyrrolidone are mixed, stirred and potassium hydroxide is added at a speed of 120 r / min and a temperature of 25° C., and the mixture is reacted for 3 h to obtain modified cellulose; 3,4-dimethoxytoluene, N-bromosuccinimide and carbon tetrachloride are mixed evenly, reacted at a speed of 200 r / min and a temperature of 80° C. for 10 min, azobisisobutyronitrile is added, and the reaction is continued for 20 h to obtain intermediate 1;
[0032] Step B3: The intermediate 1, thiourea and acetone are mixed evenly, reacted at a speed of 120 r / min and a temperature of 60°C for 3 hours, and then the filtrate is filtered to remove the filtrate, the substrate and the sodium hydroxide solution are mixed, and the reaction is carried out at a temperature of 100°C for 10 hours to obtain a modified monomer, and the modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate and deionized water are mixed evenly, and the reaction is carried out at a speed of 150 r / min and a temperature of 85°C for 10 hours, and then the modified monomer is added and the reaction is continued for 10 hours to obtain a precursor.
[0033] The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mg: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0034] The molar ratio of the amino group on the aminated cellulose and 3,4-dihydroxybenzaldehyde in step B2 is 1:1, the amount of potassium hydroxide used is 1% of the mass of 3,4-dihydroxybenzaldehyde, and the amount ratio of 3,4-dimethoxytoluene, N-bromosuccinimide, carbon tetrachloride and azobisisobutyronitrile is 2.5g:2.5g:100mL:125mg.
[0035] The amount ratio of the intermediate 1, thiourea, acetone and sodium hydroxide solution described in step B3 is 1.5mmol:1.6mmol:10mL:15mL, the mass fraction of the sodium hydroxide solution is 10%, and the amount ratio of modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate, deionized water and modified monomer is 1g:2g:4g:100mL:1.5g.
[0036] Embodiment 2: A method for preparing a low-temperature high-adhesion conductive silver paste, comprising the following steps:
[0037] Step A1: the precursor, allyl alcohol, benzoin dimethyl ether and N,N-dimethylacetamide were mixed evenly, and the mixture was reacted for 1.5 hours at a rotation speed of 60 r / min and irradiated with 365 nm ultraviolet light to obtain a modified filler;
[0038] Step A2: polycarbonate diol, isophorone diisocyanate and DMF were mixed, nitrogen was introduced for protection, and the reaction was carried out for 4 hours at a speed of 120 r / min and a temperature of 65° C., and then a modified filler was added and the reaction was continued for 4 hours, and hydroxyethyl acrylate and dibutyltin dilaurate were added and the reaction was continued for 4 hours to obtain a modified polyurethane;
[0039] Step A3: Weigh the following raw materials in parts by weight: 13 parts of modified polyurethane, 13 parts of methyl methacrylate, 4 parts of isobornyl acrylate, 1.3 parts of acrylonitrile, 1.3 parts of KH570, 0.2 parts of photoinitiator, 60 parts of silver powder and 13 parts of ethyl acetate, mix the raw materials evenly, and prepare a low-temperature and high-adhesion conductive silver paste.
[0040] The molar ratio of the thiol group and allyl alcohol on the precursor described in step A1 is 1:1, and the amount of benzoin dimethyl ether used is 2‰ of the mass of allyl alcohol.
[0041] The amount ratio of the polycarbonate diol, isophorone diisocyanate, modified filler and hydroxyethyl acrylate described in step A2 is 25mmo l:50mmo l:1.2g:18mmo l, the amount of dibutyltin dilaurate is 1‰ of the mass of hydroxyethyl acrylate, and the molecular weight of the polycarbonate diol is 1000.
[0042] The model of the photoinitiator described in step A3 is Irgacure 184D.
[0043] The precursor is prepared by the following steps:
[0044] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 80 r / min and a temperature of 105°C, stir for 4 hours, cool to 5°C, add triethylamine and p-toluenesulfonyl chloride, react for 20 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 80 r / min and a temperature of 145°C, react for 20 hours to obtain amino cellulose;
[0045] Step B2: Aminated cellulose, 3,4-dihydroxybenzaldehyde and N-methylpyrrolidone were mixed, stirred and potassium hydroxide was added at a speed of 150 r / min and a temperature of 25° C., and the mixture was reacted for 4 hours to obtain modified cellulose; 3,4-dimethoxytoluene, N-bromosuccinimide and carbon tetrachloride were mixed evenly, and the mixture was reacted at a speed of 300 r / min and a temperature of 80° C. for 10 minutes; azobisisobutyronitrile was added, and the mixture was reacted for 25 hours to obtain intermediate 1;
[0046] Step B3: The intermediate 1, thiourea and acetone are mixed evenly, reacted at a speed of 120 r / min and a temperature of 65°C for 4 hours, and then the filtrate is filtered to remove the filtrate, the substrate and the sodium hydroxide solution are mixed, and the reaction is carried out at a temperature of 105°C for 12 hours to obtain a modified monomer, and the modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate and deionized water are mixed evenly, and the reaction is carried out at a speed of 150 r / min and a temperature of 90°C for 10 hours, and then the modified monomer is added and the reaction is continued for 15 hours to obtain a precursor.
[0047] The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mg: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0048] The molar ratio of the amino group on the aminated cellulose and 3,4-dihydroxybenzaldehyde in step B2 is 1:1, the amount of potassium hydroxide used is 1% of the mass of 3,4-dihydroxybenzaldehyde, and the amount ratio of 3,4-dimethoxytoluene, N-bromosuccinimide, carbon tetrachloride and azobisisobutyronitrile is 2.5g:2.5g:100mL:125mg.
[0049] The amount ratio of the intermediate 1, thiourea, acetone and sodium hydroxide solution described in step B3 is 1.5mmol:1.6mmol:10mL:15mL, the mass fraction of the sodium hydroxide solution is 10%, and the amount ratio of modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate, deionized water and modified monomer is 1g:2g:4g:100mL:1.5g.
[0050] Embodiment 3: A method for preparing a low-temperature high-adhesion conductive silver paste, comprising the following steps:
[0051] Step A1: the precursor, allyl alcohol, benzoin dimethyl ether and N,N-dimethylacetamide were uniformly mixed, and the mixture was reacted for 1.5 hours at a rotation speed of 80 r / min and irradiated with 365 nm ultraviolet light to obtain a modified filler;
[0052] Step A2: polycarbonate diol, isophorone diisocyanate and DMF were mixed, nitrogen was introduced for protection, and the reaction was carried out for 5 hours at a speed of 150 r / min and a temperature of 70° C., and then a modified filler was added and the reaction was continued for 5 hours, and hydroxyethyl acrylate and dibutyltin dilaurate were added and the reaction was continued for 5 hours to obtain a modified polyurethane;
[0053] Step A3: Weigh the following raw materials in parts by weight: 15 parts of modified polyurethane, 15 parts of methyl methacrylate, 5 parts of isobornyl acrylate, 1.5 parts of acrylonitrile, 1.5 parts of KH570, 0.3 parts of photoinitiator, 65 parts of silver powder and 15 parts of ethyl acetate, mix the raw materials evenly, and prepare a low-temperature and high-adhesion conductive silver paste.
[0054] The molar ratio of the thiol group and allyl alcohol on the precursor described in step A1 is 1:1, and the amount of benzoin dimethyl ether used is 2‰ of the mass of allyl alcohol.
[0055] The amount ratio of the polycarbonate diol, isophorone diisocyanate, modified filler and hydroxyethyl acrylate described in step A2 is 25mmo l:50mmo l:1.2g:18mmo l, the amount of dibutyltin dilaurate is 1‰ of the mass of hydroxyethyl acrylate, and the molecular weight of the polycarbonate diol is 1000.
[0056] The photoinitiators in step A3 are DC369, Irgacure184D and Irgacure500.
[0057] The precursor is prepared by the following steps:
[0058] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 80 r / min and a temperature of 110°C, stir for 5 hours, cool to 5°C, add triethylamine and p-toluenesulfonyl chloride, react for 25 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 80 r / min and a temperature of 150°C, react for 25 hours to obtain amino cellulose;
[0059] Step B2: Aminated cellulose, 3,4-dihydroxybenzaldehyde and N-methylpyrrolidone were mixed, stirred and potassium hydroxide was added at a speed of 150 r / min and a temperature of 30° C., and the mixture was reacted for 5 h to obtain modified cellulose; 3,4-dimethoxytoluene, N-bromosuccinimide and carbon tetrachloride were mixed evenly, and the mixture was reacted at a speed of 300 r / min and a temperature of 85° C. for 15 min, azobisisobutyronitrile was added, and the mixture was reacted for 25 h to obtain intermediate 1;
[0060] Step B3: The intermediate 1, thiourea and acetone are mixed evenly, reacted at a speed of 150 r / min and a temperature of 65°C for 5 hours, and then the filtrate is filtered to remove the filtrate, the substrate and the sodium hydroxide solution are mixed, and the reaction is carried out at a temperature of 110°C for 12 hours to obtain a modified monomer, and the modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate and deionized water are mixed evenly, and the reaction is carried out at a speed of 200 r / min and a temperature of 90°C for 15 hours, and then the modified monomer is added and the reaction is continued for 15 hours to obtain a precursor.
[0061] The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mg: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0062] The molar ratio of the amino group on the aminated cellulose and 3,4-dihydroxybenzaldehyde in step B2 is 1:1, the amount of potassium hydroxide used is 1% of the mass of 3,4-dihydroxybenzaldehyde, and the amount ratio of 3,4-dimethoxytoluene, N-bromosuccinimide, carbon tetrachloride and azobisisobutyronitrile is 2.5g:2.5g:100mL:125mg.
[0063] The amount ratio of the intermediate 1, thiourea, acetone and sodium hydroxide solution described in step B3 is 1.5mmol:1.6mmol:10mL:15mL, the mass fraction of the sodium hydroxide solution is 10%, and the amount ratio of modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate, deionized water and modified monomer is 1g:2g:4g:100mL:1.5g.
[0064] Comparative Example 1: Compared with Example 1, KH570 was not added in this comparative example, and the remaining steps were the same.
[0065] Comparative Example 2: Compared with Example 1, no acrylonitrile was added in this comparative example, and the remaining steps were the same.
[0066] Comparative Example 3: Compared with Example 1, this comparative example uses amino cellulose instead of modified filler, and the other steps are the same.
[0067] Comparative Example 4: Compared with Example 1, p-methylcatechol was used to replace the modified monomer, and the remaining steps were the same.
[0068] The conductive silver paste prepared in Examples 1-3 and Comparative Examples 1-4 was brushed onto a PET film with a thickness of 50 μm and irradiated for 30 seconds under 365 nm ultraviolet light to prepare a sample. The resistivity of the sample was measured using an RTS-8 four-probe tester. The adhesion was tested in accordance with the standard of GB / T9286-2021. The test results are shown in Table 1 below.
[0069] Table 1
[0070]
[0071] It can be seen from Table 1 above that the present invention has good conductive properties and good adhesion effect.
[0072] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a low-temperature high-adhesion conductive silver paste, characterized in that: The specific steps include: Step A1: mixing a precursor, allyl alcohol, benzoin dimethyl ether and N,N-dimethylacetamide to obtain a modified filler; Step A2: polycarbonate diol, isophorone diisocyanate and DMF are mixed, nitrogen is introduced for protection, and after the reaction, a modified filler is added, the reaction is continued, hydroxyethyl acrylate and dibutyltin dilaurate are added, and the reaction is continued to obtain a modified polyurethane; Step A3: Weigh the following raw materials in parts by weight: 10-15 parts of modified polyurethane, 10-15 parts of methyl methacrylate, 3-5 parts of isobornyl acrylate, 1-1.5 parts of acrylonitrile, 1-1.5 parts of KH570, 0.1-0.3 parts of photoinitiator, 55-65 parts of silver powder and 10-15 parts of ethyl acetate, mix the raw materials evenly, and prepare a low-temperature and high-adhesion conductive silver paste.
2. The method for preparing a low-temperature high-adhesion conductive silver paste according to claim 1, characterized in that: The molar ratio of the thiol group and the allyl alcohol on the precursor described in step A1 is 1:
1.
3. The method for preparing a low-temperature high-adhesion conductive silver paste according to claim 1, characterized in that: The amount ratio of the polycarbonate diol, isophorone diisocyanate, modified filler and hydroxyethyl acrylate described in step A2 is 25mmol:50mmol:1.2g:18mmol.
4. The method for preparing a low-temperature high-adhesion conductive silver paste according to claim 1, characterized in that: The precursor is prepared by the following steps: Step B1: dispersing cellulose in N,N-dimethylacetamide, introducing nitrogen protection, stirring and adding anhydrous lithium chloride, stirring, cooling and adding triethylamine and p-toluenesulfonyl chloride to react to obtain pretreated cellulose, dispersing the pretreated cellulose in N,N-dimethylacetamide, stirring and adding ammonia water to react to obtain amino cellulose; Step B2: Amination cellulose, 3,4-dihydroxybenzaldehyde and N-methylpyrrolidone are mixed and stirred, and potassium hydroxide is added to react to obtain modified cellulose, 3,4-dimethoxytoluene, N-bromosuccinimide and carbon tetrachloride are mixed and reacted, azobisisobutyronitrile is added, and the reaction is continued to obtain intermediate 1; Step B3: After the intermediate 1, thiourea and acetone are mixed and reacted, the filtrate is filtered to remove the filtrate, the substrate and sodium hydroxide solution are mixed and reacted to obtain a modified monomer, and after the modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate and deionized water are mixed and reacted, the modified monomer is added, and the reaction is continued to obtain a precursor.
5. The method for preparing a low-temperature high-adhesion conductive silver paste according to claim 4, characterized in that: The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, and the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mg: 10 mL: 20 mL.
6. The method for preparing a low-temperature high-adhesion conductive silver paste according to claim 4, characterized in that: The molar ratio of the amino group on the aminated cellulose and 3,4-dihydroxybenzaldehyde in step B2 is 1:1, and the amount ratio of 3,4-dimethoxytoluene, N-bromosuccinimide, carbon tetrachloride and azobisisobutyronitrile is 2.5g:2.5g:100mL:125mg.
7. The method for preparing a low-temperature high-adhesion conductive silver paste according to claim 4, characterized in that: The amount ratio of the intermediate 1, thiourea, acetone and sodium hydroxide solution described in step B3 is 1.5mmol:1.6mmol:10mL:15mL, and the amount ratio of modified cellulose, 2,3,6,7,10,11-hexahydroxytriphenylene hydrate, copper trifluoroacetylacetonate, deionized water and modified monomer is 1g:2g:4g:100mL:1.5g.
8. A low-temperature high-adhesion conductive silver paste, characterized in that: Prepared according to any one of claims 1 to 7.
Citation Information
Cited By
Conductive silver paste containing conductive polymer and silver powder and preparation method thereof
CN121416156A